(untitled) (Research, Society and Development, 2023)
This study aimed to develop a flowchart for the initial care of adult burn patients at the University Hospital of Maringá. Method: To this end, an integrative literature review was conducted from 2012 to 2022, with a qualitative approach of full articles in English, Portuguese, and Spanish available in the SciELO (Scientific Electronic Library Online), PubMed/Medline (Online System for Search and Analysis of Medical Literature), LILACS (Latin American and Caribbean Literature on Health Sciences), CAPES Periodical Portal databases. As descriptors were used the terms: Guidelines (Guideline); Burns (Burn); Emergency (emergency); Burn Units (Burn Units). As exclusion criteria: studies patients aged <18 years, burn in eyes, and articles of insufficient evidence. Results: With this review 90 studies were identified, of which, 11 were selected, separating duplicates, reading titles and abstract. Of these, 8/11 described the types of cleaning and dressings used in dressings, 5/11 recommended the Advanced Trauma Life Support (ATLS) principles for initial anamnesis, 6/11 used the Parkland formula for volume replacement, 3/11 indicated the tetanus vaccine and application of heparin as prevention. Regarding analgesia, 5/11 articles suggest using intravenous opioids and, as an alternative, non-pharmacological treatments. With the perspective of improving and standardizing care, 2/11 described the importance of training the multidisciplinary team to assist the burn patient. Conclusion: It is concluded then that few studies describe the first care of burned patients and it is necessary to develop a flowchart to standardize care.